Perkembangan Metodologi Penelitian Kontemporer Dan Implikasinya Terhadap Mutu Publikasi Ilmiah: Sebuah Kajian Literatur Sistematis - A Ansorullah; Daud Ridwan; Siti Qomariatul Munawaroh; Ahsan Hakim (Education Reserach Center, 2025)
The development of contemporary research methodologies has undergone significant transformation in response to advances in digital technology, the use of big data, and increasing demands for transparency, replicability, and academic integrity in scientific publications. This study aims to systematically examine the evolution of modern research methodologies and their implications for the quality of scientific publications. A Systematic Literature Review (SLR) approach was employed by reviewing literature from reputable international databases published over the past ten years. The selected studies were analyzed using qualitative content analysis to identify major methodological trends and emerging epistemological challenges. The findings indicate that mixed-methods approaches, artificial intelligence–based analytics, big data utilization, and the adoption of open science principles have become dominant features of contemporary research. These results underscore that improvements in publication quality are strongly influenced by the selection of appropriate methodological approaches, strengthened analytical rigor, transparent reporting practices, and sustained institutional support.